FISA and the Olympic Movement - Rolland, J.-C. (2015 Youth Coaches Conference - Beijing, China, 2015)
This presentation presents - The FISA vision: To encourage the development of the sport of rowing and strengthen the bonds that unite those who practice it. - The mission: To make rowing a universally practised and globally relevant sport. To spread the sport in all its forms. - The objectives: To DEVELOP. PROMOTE. PRESENT. GOVERN the sport of rowing.